2017
DOI: 10.1063/1.4984927
|View full text |Cite
|
Sign up to set email alerts
|

Revival of oscillations from deaths in diffusively coupled nonlinear systems: Theory and experiment

Abstract: Amplitude death (AD) and oscillation death (OD) are two structurally different oscillation quenching phenomena in coupled nonlinear systems. As a reverse issue of AD and OD, revival of oscillations from deaths attracts an increasing attention recently. In this paper, we clearly disclose that a time delay in the self-feedback component of the coupling destabilizes not only AD but also OD, and even the AD to OD transition in paradigmatic models of coupled Stuart-Landau oscillators under diverse death configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In fact, network concepts related to “amplitude death” and “oscillation death” might be applicable to the observed surge in neurophysiological coherence just before functional network breakdown in the brain around the time of death. Using a Stuart‐Landau model, one investigation described the dynamics of how such oscillations can spontaneously “revive,” [41] while another study described how the revival of such oscillations can be accompanied by rhythmicity and dynamic activity across the network [42]. These concepts have also been instantiated in neuronal models, with the conclusion that at a certain point of neuronal inhibition in a sparsely connected network, there is a counterintuitive “rebirth” of neuronal activity [43] that is manifested across the network.…”
Section: Possible Mechanisms Of Plmentioning
confidence: 99%
“…In fact, network concepts related to “amplitude death” and “oscillation death” might be applicable to the observed surge in neurophysiological coherence just before functional network breakdown in the brain around the time of death. Using a Stuart‐Landau model, one investigation described the dynamics of how such oscillations can spontaneously “revive,” [41] while another study described how the revival of such oscillations can be accompanied by rhythmicity and dynamic activity across the network [42]. These concepts have also been instantiated in neuronal models, with the conclusion that at a certain point of neuronal inhibition in a sparsely connected network, there is a counterintuitive “rebirth” of neuronal activity [43] that is manifested across the network.…”
Section: Possible Mechanisms Of Plmentioning
confidence: 99%
“…This suggests that there should be some proper prescription to resurrect oscillation from such quenched states. Regarding this issue of revival of oscillations, there exists some significant contributions [36][37][38][39][40][41][42]. In the present article, we introduce a feedback parameter γ in the coupling function for reviving the oscillation state from amplitude death state, the influence of which in doing so has been validated earlier [39][40][41][42] for networks possessing stationary connections.…”
mentioning
confidence: 72%
“…This suggests that there should be some proper prescription to resurrect oscillation from such quenched states. Regarding this issue of revival of oscillations, there exists some significant contributions [36][37][38][39][40][41][42].…”
mentioning
confidence: 99%
“…The internal self-feedback delay appears because sometimes the system needs a finite time to process the received signal and then act on it. It is demonstrated that such type of local self-feedback delay acts as negative feedback and plays a crucial role in reviving oscillations or amplitude death and oscillation death 34 . In comparison to propagation delay, the effects of selffeedback delay in coupling are very less explored.…”
Section: Introductionmentioning
confidence: 99%